The First-Principles Study of External Strain Tuning the Electronic and Optical Properties of the 2D MoTe2/PtS2 van der Waals Heterostructure - Zhang, Li; Ren, Kai; Cheng, Haiyan; Cui, Zhen; Li, Jianping (Frontiers in Chemistry, 2022)
Two-dimensional van der Waals (vdW) heterostructures reveal novel properties due to their unique interface, which have attracted extensive focus. In this work, the first-principles methods are explored to investigate the electronic and the optical abilities of the heterostructure constructed by monolayered MoTe2 and PtS2. Then, the external biaxial strain is employed on the MoTe2/PtS2 heterostructure, which can persist intrinsic type-II band structure and decrease the bandgap. In particular, the MoTe2/PtS2 vdW heterostructure exhibits suitable band edge energy for the redox reaction for water splitting at pH 0, while it is also desirable for that at pH 7 under decent compressive stress. More importantly, the MoTe2/PtS2 vdW heterostructure shows classy solar-to-hydrogen efficiency and the light absorption properties can further be enhanced by the strain. Our results show an effective theoretical strategy to tune the electronic and optical performance of the 2D heterostructure, which can be used in energy conversion such as automotive battery system.